A new species of Brachygasterina Macquart from Colombia, and description of the males of B. stuebeli Röder and B. muisca Soares & Carvalho (Diptera: Muscidae) - Pérez, Sandra; Wolff, Marta; de Carvalho, Claudio J. B. (Zootaxa, 2012)
Here we describe the new species Brachygasterina setulosa Pérez, Wolff & Carvalho, sp. nov. from Colombia, Cundinamarca Department, Parque Nacional Natural Sumapaz, at 3560 m above sea level. Descriptions of males of B. stuebeli (Röder) and B. muisca Soares & Carvalho are also included. Currently, 11 species of Brachygasterina Macquart are known from South America, six of which occur in the highlands of Ecuador, Colombia and Venezuela.